5-Minute Yoga: A More Energetic, Focused, and Balanced You in Just 5 Minutes a Day - Adams Media (Firm) (5-Minute, 2018)
Find the perfect way to take a meaningful break and relax your mind and body in just five minutes with this handy, portable guide featuring 100 different yoga sequences to improve focus, mood, energy level, and more. In 5-Minute Yoga, you'll find 100 yoga sequences that can help you refresh your body and mind in only five minutes. Each sequence--designed to provide a specific benefit to your body, mind, and spirit--contains a detailed explanation with illustrations of each pose so it's easy to follow along. This guide also includes a glossary with illustrations and short explanations of each yoga pose featured throughout the book--perfect for beginners Whether you need a quick moment of peace during a hectic day or a chance to promote strength and flexibility to benefit your body, 5-Minute Yoga is sure to give you the restart you need.